2020
DOI: 10.3390/genes11101200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Quantitative Trait Loci for Germination and Coleoptile Length under Low-Temperature Condition Using Introgression Lines Derived from an Interspecific Cross in Rice

Abstract: Previously, five putative quantitative trait loci (QTLs) for low-temperature germination (LTG) have been detected using 96 BC3F8 lines derived from an interspecific cross between the Korean japonica cultivar “Hwaseong” and Oryza rufipogon. In the present study, two introgression lines, CR1517 and CR1518, were used as parents to detect additional QTLs and analyze interactions among QTLs for LTG. The F2 population (154 plants) along with parental lines, Hwaseong and O. rufipogon, were evaluated for LTG and coleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Bertin [25] reported a positive correlation between early seedling cold tolerance with flowering stage cold tolerance. According to Akhtamov's findings [26], the insertion of advantageous O. rufipogon alleles might speed up the development of rice cultivars with high levels of coleoptile elongation and low-temperature germination (LTG) in japonica cultivars. The outcomes demonstrated that the effects of low temperature differed across genotypes investigated in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bertin [25] reported a positive correlation between early seedling cold tolerance with flowering stage cold tolerance. According to Akhtamov's findings [26], the insertion of advantageous O. rufipogon alleles might speed up the development of rice cultivars with high levels of coleoptile elongation and low-temperature germination (LTG) in japonica cultivars. The outcomes demonstrated that the effects of low temperature differed across genotypes investigated in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the measurements of PH and FLL under cold stress set the data under normal-temperature condition as the control, whereas the measurements of PH and FLL under BR-combined cold treatment set the data under normal-temperature condition and cold stress as the controls, respectively. This was done to obtain more comprehensive QTLs ( Kim et al, 1999 ; Qiao et al, 2004 ; Akhtamov et al, 2020 ; Najeeb et al, 2020 ; Pan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of cold tolerance at germination and bud burst stages was conducted based on previous studies with minor changes ( Kim et al, 1999 ; Qiao et al, 2004 ; Akhtamov et al, 2020 ; Najeeb et al, 2020 ; Pan et al, 2020 ). Seeds of each accession from the BRILs were placed in a drying oven at 50°C for 72 h to break dormancy, and surface-sterilized in 1% NaClO solution for 10 min, followed by washing three times in sterilized distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 100 plumped seeds of each rice accession were extracted and spread on a round wet filter paper and kept at 15 °C and in darkness for germination. The number of germinated seeds was recorded daily from D6 to D10 with a seed shoot or root exceeding 0.1 cm considered a germinated seed ( Wang et al, 2018c ; Akhtamov et al, 2020 ; Najeeb et al, 2020 ). Seed germination rate = germinated seeds/100.…”
Section: Methodsmentioning
confidence: 99%